PENINGKATAN KUALITAS BAHASA INGGRIS GURU SEKOLAH DASAR DI KOTA PADANG MELALUI PELATIHAN SINGKAT - Syarif, Hermawati (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
Â This article aims at describing the result of processing English training to classroom teachers of the elementary schools of Padang City for the sake of their English quality. By training the participants basic knowledge of Simple English and the skills to express it to be transferred to the fourth grade of elementary students, and by monitoring them in ongoing activities, it was found that nine out of the twenty participants had the potential to develop their English competence and skills in the future to fulfill the formation of English teachers at elementary schools. For temporary, they are recommended to teach English at their schools while they are developing their competence. To the office educational affairs, it is suggested to select the ones who have the interest in English to be trained.